(untitled) (Journal of Student Affairs in Africa, 2021)
There has always been pressure on higher education institutions to enhance the employability of graduates and to instil knowledge, skills, and attributes that will be beneficial to future employers. The impact of Covid‑19 on a global, national, and local level is placing even more pressure on the topic of employability. Graduates are uncertain about job availability and there is a need for career guidance. After a national and local shutdown of university campuses in 2015 and 2016 due to #FeesMustFall, Career Services staff at the University of the Free State designed and created online work readiness programmes in order for students to continue with work preparations, no matter what the circumstances. In 2018, the first topics on CV‑writing and job interview skills were rolled out online and made available to all registered students; each semester, two additional topics were added. By the time Covid‑19 led to a national lockdown in South Africa in March 2020, the transition to online work readiness programmes was fairly easy. The purpose of this study is to determine the impact of the online work readiness programmes offered on the Blackboard platform from April to June 2020 during the Covid‑19 pandemic and national lockdown. This article will provide an analysis of a questionnaire conducted with willing participants who have engaged and worked through the online work readiness programmes from April to June 2020, to investigate the impact on graduates’ readiness for the world of work. Through the survey, students shared their learning experiences and the influence it has had on their career planning. It is believed that the findings of this research study will create a deeper understanding of how career services, as a particular functional area in student affairs, can reposition itself during uncertain times to remain responsive to the needs of students.